Prognostic value of the ferroptosis-related gene SLC2A3 in gastric cancer and related immune mechanisms - Lin, Liubing; Que, Renye; Wang, Jian; Zhu, Yi; Liu, Xiaolin; Xu, Rongzhong (Frontiers in Genetics, 2022)
Background: SLC2A3 is a ferroptosis marker and is involved into glucose transmembrane transport. However, the impact of SLC2A3 on the prognosis of cancer patients remains unclear. The objective of our study was to explore the prognostic implication and underlying immune mechanisms of SLC2A3 in gastric cancer. Methods: The mRNA expression profiles and corresponding clinical data of gastric cancer patients were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. The differentially expressed genes (DEGs) related to SLC2A3 were identified through the “limma” R package. Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), gene set enrichment analysis (GSEA) and Gene set variation analysis (GSVA) were used to explore underlying mechanisms. The protein interaction network and miRNA interaction network were analyzed by Cytoscape software. Immune cell infiltration assessment analysis was performed by the single-sample gene set enrichment analysis (ssGSEA). Univariate and multivariate Cox regression analyses were conducted to analyze the relationship of SLC2A3 and prognosis. Results: SLC2A3 was highly expressed in tumor tissues that was associated with an unfavorable prognosis of the patients with gastric cancer. Functional enrichment analysis showed that SLC2A3 was related to cytokine-cytokine receptor interaction, EMT, T cell receptor signaling pathway, B cell receptor signaling pathway, and immune checkpoints. SLC2A3 was also involved into the immune response regulation and was regulated by multiple miRNAs including miR-195-5p, miR-106a-5p, miR-424-5p, and miR-16-5p. Univariate and multivariate Cox regression analyses indicated that SLC2A3 could be used as an independent prognostic factor to predict the prognosis of patients with gastric cancer. Conclusion: The results of our study indicated that SLC2A3 can be used for prognostic prediction in the patients with gastric cancer. SLC2A3 and it-related miRNAs are potential prognostic biomarkers and therapeutic targets.